Full-scale production and material properties of ultra-high-performance fiber-reinforced concrete (UHPFRC) for rehabilitation of bridge decks in Norway - Lande, Ingrid; Thorstensen, Rein Terje; Petersen, Berit Gudding; Kanstad, Terje (Frontiers in Built Environment, 2025)
This paper is a presentation of an investigation into the suitability of locally produced ultra-high-performance fiber-reinforced concrete (UHPFRC) for the rehabilitation of deteriorated concrete bridge decks in Norway. Full-scale production was conducted at a conventional ready-mix concrete plant using mostly locally available materials from silos at the plant. Material properties relevant for bridge deck rehabilitation were investigated, including compressive strength, residual flexural strength, E-modulus, shrinkage, and resistance to chloride ion penetration. These results were compared to earlier experiences at laboratory scale. The findings indicate that full-scale production of UHPFRC with locally available constituents is achievable using common facilities for ready-mixed concrete, including mixing, transportation, and pumping in quantities appropriate for industrialized bridge deck rehabilitation. The applied UHPFRC mix design was found suitable for bridge rehabilitation, considering compressive and flexural strength, shrinkage, and durability evaluated by resistance against chloride migration. Up to approximately 3 vol% of micro steel fibers (225 kg/m3) were stepwise added, achieving a castable and self-leveling UHPFRC mix. Self-leveling mixes are not suitable for applications in slopes, which are common for bridge decks. Adjustments to the mix design are necessary to achieve thixotropy. Some additional material properties remain to be evaluated, such as the bond between the old concrete substrate and the new UHPFRC layer. This is being investigated in the next stage of the project.